Flexural buckling of sandwich beams with thermal-induced non-uniform sectional properties. (September 2019) - Chen, Zhenlei; Li, Jiancheng; Sun, Longfei; Li, Long-yuan
Abstract: An analytical study is presented on the flexural buckling of sandwich beams considering thermal-induced non-uniform cross-sectional properties. The formula for determining the buckling loads of sandwich beams under a linearly varied non-uniform temperature distribution scenario, both with and without considering the influence of transverse shear deformation, is derived. The effects of local reductions in Young's modulus and shear modulus on the flexural buckling of sandwich beams are discussed. The obtained results demonstrate the importance of considering non-uniform cross-sectional properties and associated shear effects in the buckling analysis of sandwich beams when they are exposed to a thermal environment. Highlights: An analytical solution is presented for calculating buckling load of sandwich beams subjected to axially compressive load. It demonstrates that the bending stiffness of middle part of sandwich beams has some positive effect on the buckling of beams. Temperature-induced reduction of Young's modulus and shear modulus can significantly reduce the critical load of beams. Transverse shear deformation of middle part of sandwich beams has a large effect on the critical load of the beams.